2006
DOI: 10.1101/gad.1447606
|View full text |Cite
|
Sign up to set email alerts
|

Red-Hed regulation: recombinase Rad51, though capable of playing the leading role, may be relegated to supporting Dmc1 in budding yeast meiosis: Figure 1.

Abstract: DNA strand exchange is the central process of homologous recombination. In budding yeast, this reaction is catalyzed by the recombinases Rad51 and Dmc1. Rad51 is responsible for recombinational repair of DNA damage during mitosis and is also important during meiotic recombination. Dmc1 is only expressed during meiosis and is required for meiotic recombination. The discovery that these two different recombinases are needed for normal levels of meiotic recombination in budding yeast raised the question of how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 55 publications
3
66
0
Order By: Relevance
“…Studies have demonstrated that the RecA homologs function in a coordinated manner to promote early steps in the meiotic recombination pathway (Neale and Keeney 2006;Sheridan and Bishop 2006), a key feature of which is a preferential bias that ensures that recombination occurs between homologous nonsister chromosomes (Schwacha and Kleckner 1997). In budding yeast, it is proposed that an axis-associated complex of Hop1, Red1, and Mek1 actively suppress DMC1-independent strand invasion during meiosis (Niu et al 2005).…”
Section: Normal Levels Of Interhomolog Recombination Require Asy1mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that the RecA homologs function in a coordinated manner to promote early steps in the meiotic recombination pathway (Neale and Keeney 2006;Sheridan and Bishop 2006), a key feature of which is a preferential bias that ensures that recombination occurs between homologous nonsister chromosomes (Schwacha and Kleckner 1997). In budding yeast, it is proposed that an axis-associated complex of Hop1, Red1, and Mek1 actively suppress DMC1-independent strand invasion during meiosis (Niu et al 2005).…”
Section: Normal Levels Of Interhomolog Recombination Require Asy1mentioning
confidence: 99%
“…Nevertheless, efficient repair of all the meiotic DSBs does appear to require Rad51 activity. Hence, it has been proposed that the barrier to intersister repair is eventually lifted, such that Rad51-mediated repair can occur (Sheridan and Bishop 2006). Similarly, in Arabidopsis, AtRAD51 is essential to ensure that the repair of meiotic DSBs is efficient, as DNA fragmentation is observed in an Atrad51 mutant (Li et al 2004).…”
Section: Normal Levels Of Interhomolog Recombination Require Asy1mentioning
confidence: 99%
“…It has been suggested that Red1, Hop1, and Mek1 proteins that are associated with the axial elements suppress Dmc1-independent recombination in an indirect fashion, possibly by influencing the structure of meiotic chromosomes (for review, see Sheridan and Bishop 2006). In contrast, Hed1 appears to regulate meiotic recombination via a direct action on Rad51 (Tsubouchi and Roeder 2006).…”
Section: Mechanistic Basis For Hed1-dependent Recombination Regulationmentioning
confidence: 99%
“…Some of these recombination events lead to the formation of interhomolog crossovers that are crucial for linking the homologous chromosomes, to ensure their proper alignment on the spindle apparatus and faithful disjunction in the first meiotic division. As such, interhomolog crossover recombination is indispensable for the successful execution of meiosis (Keeney et al 1997;Neale and Keeney 2006;Sheridan and Bishop 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation